Safety and Efficacy of a Scar Cream Consisting of Highly Selective Growth Factors Within a Silicone Cream Matrix: A Double-Blinded, Randomized, Multicenter Study. (31st July 2018) - Zoumalan, Christopher I; Tadayon, Shiva C; Roostaeian, Jason; Rossi, Anthony M; Gabriel, Allen
Abstract: Background: Several growth factors and hyaluronic acid are implicated in fetal scarless healing. Whether these factors can be applied to an adult scar to improve scar characteristics is unknown. Objectives: This study compared the efficacy and safety of SKN2017B, a proprietary topical cream consisting of selective synthetic recombinant human growth factors and hyaluronic acid in a silicone base containing a specifically formulated silicone cream for postsurgical scar treatment. Methods: In this prospective, randomized, controlled, double-blinded study, unilateral or bilateral facial or truncal scars in adult surgical patients were randomly treated with SKN2017B or silicone cream. Study investigators, study patients, and 2 independent reviewers assessed improvement in scar characteristics after 4 and 12 weeks of treatment. Results: Forty-nine bilateral and 12 unilateral scars in 45 patients were treated with SKN2017B or silicone. At 12 weeks, investigators rated 74% of scars treated with SKN2017B as showing overall improvement vs 54% of silicone-treated scars, a 73% relative improvement with SKN2017B ( P < 0.0001). Patients rated a moderate-to-significant improvement in 85% of SKN2017B-treated scars vs 51% of silicone-treated scars, a 67% relative improvement with SKN2017B ( P < 0.001). Independent reviewers rated 87% of scars treated with SKN2017B to be better overall vs 1% of scars treated with silicone ( P < 0.0001). There were no tolerability issues or adverse reactions with either cream. Conclusions: SKN2017B consists of highly selective growth factors within a silicone cream matrix and is well tolerated and effective for surgical scar management. Level of Evidence: 1: